# Class 12 RD Sharma Solutions – Chapter 2 Functions – Exercise 2.2

• Last Updated : 02 Feb, 2021

### Question 1(i). Find g o f and f o g when f: R -> R and g: R -> R is defined by f(x) = 2x + 3 and g(x) = x2 + 5

Solution:

f: R -> R and g: R -> R

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12.

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

Therefore, f o g: R -> R and g o f: R -> R

Now, f(x) = 2x + 3 and g(x) = x2 + 5

g o f(x) = g(2x + 3) =(2x + 3)2 + 5

=> g o f(x) = 4x2 + 12x + 14

f o g(x) = f(g(x)) = f(x2 + 5) = 2(x2 + 5) + 3

=> f o g(x) = 2x2 + 13

### Question 1(ii). Find g o f and f o g when f: R -> R and g: R -> R is defined by f(x) = 2x + x2 and g(x) = x3

Solution:

f(x) = 2x + x2 and g(x) = x3

g o f(x) = g(f(x)) = g(2x + x2)

g o f(x) =(2x + x2)3

f o g(x) = f(g(x)) = f(x3)

f o g(x) = 2x3 + x6

### Question 1(iii). Find g o f and f o g when f: R -> R and g: R -> R is defined by f(x) = x2 + 8 and g(x) = 3x3 + 1

Solution:

f(x) = x2 + 8 and g(x) = 3x3 + 1

Thus, g o f(x) = g [f(x)]

=> g o f(x) = g [x2 + 8]

=> g o f(x) = 3 [x2 + 8]3 + 1

Similarly, f o g(x) = f [g(x)]

=> f o g(x) = f [3x3 + 1]

=> f o g(x) = [3x3 + 1]2 + 8

=> f o g(x) = [9x6 + 1 + 6x3] + 8

=> f o g(x) = 9x6 + 6x3 + 9

### Question 1(iv). Find g o f and f o g when f: R -> R and g: R -> R is defined by f(x) = x and g(x) = | x |

Solution:

f(x) = x and g(x) = | x |

Now, g o f = g(f(x)) = g(x)

g o f(x) = | x |

g o f(x) = | x |

and, f o g(x) = f(g(x)) = f(x)

f o g(x) = | x |

### Question 1(v). Find g o f and f o g when f: R -> R and g: R -> R is defined by f(x) = x2 + 2x – 3 and g(x) = 3x – 4

Solution:

f(x) = x2 + 2x – 3 and g(x) = 3x – 4

Now, g o f(x) = g(f(x)) = g(x2 + 2x – 3)

g o f(x) = 3(x2 + 2x – 3) -4

g o f(x) = 3x2 + 6x – 13

and, f o g(x) = f(g(x)) = f(3x – 4)

f o g(x) =(3x – 4)2 + 2(3x – 4) – 3

= gx2 + 16 – 24x + 6x – 8 – 3

f o g(x) = 9x2 – 18x + 5

### Question 1(vi). Find g o f and f o g when f: R -> R and g: R -> R is defined by f(x) = 8x3 and g(x) = x1/3

Solution:

f(x) = 8x3 and g(x) = x1/3

Now, g o f(x) = g(f(x)) = g(8x3)

=(8x,3),1/3

g o f(x) = 2x

and, f o g(x) = f(g(x)) = f(x1/3)

= 8(x1/3)3

f o g(x) = 8x

### Question 2. Let f = {(3, 1), (9, 3), (12, 4)} and g = {(1, 3), (3, 3), (4, 9), (5, 9)} Show that g o f and f o g are both defined. Also, find f o g and g o f.

Solution:

Let f = {(3, 1),(9, 3),(12, 4)} and

g = {(1, 3),(3, 3),(4, 9),(5, 9)

Now,

range of f = {1, 3, 4}

domain of f = {3, 9, 12}

range of g = {3, 9}

domain of g = {1, 3, 4, 5}

since, range of f ⊂ domain of g

Therefore g o f in well defined.

range of g ⊂ domain of g

g o f in well defined.

Now g o f = {(3, 3),(9, 3),(12, 9)}

f o g = {(1, 1),(3, 1),(4, 3),(5, 3)}

### Question 3. Let f = {(1, -1), (4, -2), (9, -3), (16, 4)} and g = {(-1, -2), (-2, -4), (-3, -6), (4, 8)} Show that g o f is defined while f o g is not defined. Also, find g o f.

Solution:

We have,

f = {(1, -1),(4, -2),(9, -3),(16, 4)} and

g = {(-1, -2),(-2, -4),(-3, -6),(4, 8)}

Now,

Domain of f = {1, 4, 9, 16}

Range of f = {-1, -2, -3, 4}

Domain of g = {-1, -2, -3, 4}

Range of g = {-2, -4, -6, 8}

Clearly range of f = domain of g

Therefore, g o f is defined.

but, range of g != domain of f

Therefore, f o g is not defined.

Now,

g o f(1) = g(-1) = -2

g o f(4) = g(-2) = -4

g o f(g) = g(-3) = -6

g o f(16) = g(4) = 8

Therefore, g o f = {(1, -2),(4, -4),(9, -6),(16, 8)}

### Question 4. Let A = {a, b, c}, B = {u, v, w} and let f and g be two functions from A to B and from B to A, respectively, defined as: f = {(a, v), (b, u), (c, w)},g = {(u, b), (v, a), (w, x)}. Show that f and g both are bijections and find f o g and g o f.

Solution:

A = {a, b, c}, B = {u, v, w} and

f = A -> B and g: B -> A defined by

f = {(a, v),(b, u),(c, w)} and

g = {(u, b) .(v, a),(w, c)}

For both f and g, different elements of domain have different images

Therefore, f and g are one-one

Again for each element in co-domain of f and g, there in a preimage in domain

Therefore, f and g are onto

So f and f are bijectives,

Now,

g o f = {(a, a),(b, b),(c, c)} and

f o g = {(u, u),(v, v),(w, w)}

### Question 5. Find f o g(2) and g o f(1) when: f: R -> R ; f(x) = x2 + 8 and g: R -> R ; g(x) = 3 x3 + 1.

Solution:

We have,

f: R -> R given by f(x) = x2 + 8 and

g: R -> R given by g(x) = 3x3 + 1

Therefore,

f o g(x) = f(g(x)) = f(3x3 + 1)

=(3x3 + 1)2 + 8

Therefore, f o g(2) =(3 * 8 + 1)2 + 8 = 625 + 8 = 633

Again

g o f(x) = g(f(x)) = g(x2 + 8)

= 3(x2 + 8)3 + 1

g o f(1) = 3(1 + 8)3 + 1 = 2188

### Question 6. Let R+ be the set of all non-negative real numbers . if: R+ -> R+ and g: R+ -> R+ are defined as f(x) = x2 and g(x) = +√x, find f o g and g o f . Are they equal functions ?

Solution:

We have, f: R+ -> R+ given by

f(x) = x2

g: R+ -> R+ given by

g(x) = √x

f o g(x) = f(g(x)) = f(√x) =(√x)2 = x

Also,

g o f(x) = g(f(x)) = g(x2 ) = √x2 = x

Thus,

f o g(x) = g o f(x)

### Question 7. Let f: R -> R and g: R -> R be defined by f(x) = x2 and g(x) = x + 1. Show that f o g != g o f.

Solution:

We have f: R -> R and g: R -> R are two functions defined by f(x) = x2 and g(x) = x + 1

Now,

f o g(x) = f(g(x)) = f(x + 1) =(x + 1)2

f o g(x) = x2 + 2x + 1 —> eq(i)

g o f(x) = g(f(x)) = g(f(x)) = g(x,2) = x2 + 1 —->(ii)

from(i),(ii)

f o g != g o f

### Question 8. Let f: R -> R and g: R -> R be defined by f(x) = x + 1 and g(x) = x – 1. Show that f o g = g o f = IR.

Solution:

Let f: R -> R and g: R -> R are defined as .

f(x) = x +1 and g(x) = x – 1

Now,

f o g(x) = f(g(x)) = f(x – 1) = x – 1 + 1

= x = IR —>(i)

Again,

f o g(x) = f(g(x)) = g(x + 1) = x + 1 – 1

= x = IR —>(ii)

from i and ii

f o g = g o f = IR

### Question 9. Verify associativity for the following three mappings: f: N -> Z0(the set of non-zero integers), g: Z0 -> Q and h: Q -> R given by f(x) = 2x, g(x) = 1 / x and h(x) = ex

Solution:

We have f: N -> Z0, g: Z0 ->Q and

h: Q -> R

Also, f(x) = 2x, g(x) = 1 / x and h(x) = ex

Now, f: N -> Z0 and h o g: Z0 -> R

(h og) of: N -> R

also, g o f: N -> Q and h: Q -> R

h o(g o f): N -> R

Thus,(h o g) o f and h o(g o f) exist and are function from N to set R.

Finally,(h o g) o f(x) =(h o g)(f(x)) =(h o g)(2x)

= h(1 / 2x)

= e1/2x

Now, h o(g o f)(x) = h o(g(2x)) = h(1 / 2x)

= e1/2x

Associativity verified.

### Question 10. Consider f: N -> N, g: N -> N and h:N -> R as f(x) = 2x, g(y) = 3y + 4 and h(z) = sin z for all x, y, z ∈ N . Show that h o(g o f) =(h o g) o f .

Solution:

We have,

h o(g o f)(x) = h(g o f(x)) = h(g(f(x)))

= h(g(2x)) h(3(2x) + 4)

= h(6x + 4) = sin(6x + 4) x ∈ N

((h o g) o f)(x) =(h o g)(f(x)) =(h o g)(2x)

= h(g(2x)) == h(3(2x) + 4)

= h(6x + 4) = sin(6x + 4) x ∈ N

This shows, h o(g o f) =(h o g) o f

### Question 11. Give examples of two functions f: N -> N and g: N -> N, such that g o f is onto but f is not onto.

Solution:

Define f: N -> N by, f(x) = x + 1

And, g: N -> N by,

g(x) = x – 1 if x > 1

1 if x = 1

first show that f is not onto.

for this, consider element 1 in co – domain N . It is clear that this element is not an image of any of the elements in domain N .

Therefore, f is not onto.

Now, g o f: N -> N is defined.

### Question 12. Give examples of two functions f: N -> Z and g: Z -> Z, such that g o f is injective but g is not injective.

Solution:

Define f: N -> Z as f(x) = x and g: z -> z as g(x) = | x | .

We first show that g is not injective.

It can be observed that:

g(-1) = | -1 | = 1

g(1) = | 1 | = 1

Therefore, g(-1) = g(1), but -1 != 1 .

Therefore, g is not injective.

Now, g o f: N -> Z is defined as g o f(x) = g(f(x)) = g(x) = | x |.

let x, y E N such that g o f(x) = g o f(y) .

=> | x | = | y |

Since x and y ∈ N, both are positive.

| x | = | y | => x = y

Hence, g o f is injective

### Question 13. If f: A -> B and g: B -> C are one-one functions, show that g o f is a one – one function.

Solution:

We have f: A -> B and g: B -> C are one – one functions

Now we have to prove: g o f: A -> C in one – one

let x, y ∈ A such that

g o f(x) = g o f(y)

=> g(f(x)) = g(f(y))

=> f(x) = f(y)

x = y

Therefore, g o f is one – one function.

### Question 14. If f: A -> B and g: B -> C are onto functions, show that g o f is a onto function.

Solution:

We have, f: A -> B and g: B -> C are onto functions

Now, we need to prove: g o f: A -> C in onto

let y ∈ C, then,

g o f(x) = y

g(f(x)) = y –>(i)

Since g is onto, for each element in c, then exists a preimage in B.

g(x) = y —->(ii)

from(i) and(ii)

f(x) = ∞

Since f is onto, for each element in B there exists a preimage in A

f(x) = ∞ —>(iii)

From(ii) and(iii) we can conclude that for each y ∈ c there exists a pre image in A

Such that g o f(x) = y

Therefore, g o f is onto

My Personal Notes arrow_drop_up